2014
DOI: 10.1097/mjt.0b013e3182456d88
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Syndrome After the Use of Tramadol and Ziprasidone in a Patient With a Deep Brain Stimulator for Parkinson Disease

Abstract: Serotonin syndrome (SS) is a life-threatening adverse reaction that can result from the therapeutic use of serotonergic drugs or accidental drug interactions. Tramadol is a drug that is widely prescribed because of its low abuse potential, but physicians need to be aware of its significant potential to cause SS because it inhibits serotonin reuptake. Ziprasidone is an atypical antipsychotic that can also cause dangerous interactions to cause SS because it is not only a potent 5-HT1A agonist but also has been r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Tramadol is an analgesic widely prescribed because of its low abuse potential, but researchers found serotonin syndrome, a life-threatening adverse reaction, in a PD patient who used tramadol and ziprasidone [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tramadol is an analgesic widely prescribed because of its low abuse potential, but researchers found serotonin syndrome, a life-threatening adverse reaction, in a PD patient who used tramadol and ziprasidone [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…A clinical trial that conducted parallel comparison experiments on 14 patients demonstrated that ziprasidone is effective in ameliorating psychotic symptoms in PD patients [ 55 ]. However, serotonin syndrome occurred in a PD patient using ziprasidone for bipolar disorder [ 54 ]. Therefore, further studies are needed to evaluate the efficacy of ziprasidone for PD.…”
Section: Resultsmentioning
confidence: 99%
“…Case reports suggest that some SGAs may decrease the risk for serotonin syndrome, while other SGAs may increase the risk for serotonin syndrome. In that sense ziprasidone may be a special case, since it can inhibit serotonin reuptake and has been proposed as the single agent causing serotonin syndrome in one case [102] and as a contributing factor in two others [103,104]. Other cases suggest that withdrawal from olanzapine [105] or clozapine [106] may have contributed to serotonin syndrome.…”
Section: Pd Dis Increasing Safetymentioning
confidence: 91%
“…The exact rate of SS is unclear but is generally not expected to occur in more than 5% of the hospitalized patients [5,44,53,[96][97][98]. The (+) enantiomer of tramadol inhibits re-absorption of serotonin [99].…”
Section: Mental Status Changes (Agitation Confusion Restlessness Hmentioning
confidence: 99%